Acid‐base imbalances and the association of blood‐gas variables, electrolytes, and biochemical analytes with outcome in hospitalized calves undergoing abdominal surgery. (20th January 2023) - Trefz, Florian M.; Lausch, Corinna K.; Rieger, Anna; Giertzuch, Stine; Lorch, Annette; Constable, Peter D.
Abstract: Background: Surgical abdominal emergencies in calves are associated with a guarded prognosis and have the potential for complex metabolic derangements including acid‐base imbalances. Objectives: To perform a comprehensive analysis of acid‐base status and to assess the prognostic relevance of preoperative clinicopathologic variables in calves undergoing abdominal surgery. Animals: Hospital‐based study samples of 535 (dataset 1; DS1) and 83 calves (dataset 2; DS2). Methods: Retrospective (DS1) and prospective (DS2) case series. Results: In DS1, acidemia (pH <7.33) was present in 49.9%, whereas alkalemia (pH >7.37) was present in 30.7% of calves. Plasma L‐lactate, chloride, and serum inorganic phosphorus concentration accounted for 51.9%, 11.6% and 9.4% of the variation of venous blood pH, respectively. Classification tree analysis indicated that a negative outcome (death or euthanasia during hospitalization) was associated with venous pO2  ≤33.6 mm Hg, anion gap >18.3 and >22.9 mEq/L, serum albumin concentration ≤36.5 and ≤29.4 g/L, serum urea concentration >4.4 mmol/L, and plasma ionized calcium concentration ≤1.26 mmol/L. The area under the receiver operating characteristic curve of this model was 0.85 (95% CI: 0.82‐0.89, P  < .001) and the resulting sensitivity and specificity for the prediction of nonsurvival at the optimal probability cut‐point of 0.5 was 89.8% and 65.7%, respectively. In DS2 the model had a similar sensitivity and specificity of 90.5% and 70%, respectively. Conclusions and Clinical Importance: Clinicopathologic imbalances and associated changes of acid‐base status are common in calves with surgical abdominal emergencies and have clinical utility for the prediction of a negative postoperative outcome.